PERFORMANCE ANALYSIS OF SOLAR POWER PLANT IN GEBENG - MOHD DZUKERI, MOHAMAD IRFAN (2018)
The Malaysian government has strived to create a sustainable life for the Malaysia citizen so that they can live without interruption of natural pollution. Thus, the government has developed solar energy and the implementation of the payment tariff mechanism for renewable energy or FiT power under the gazette Renewable Energy Act is expected to help further increase the use of solar energy in the country. Therefore, PETRONAS has taken steps to increase in energy production in Malaysia by introducing renewable energy program on 2014 namely the Voltage Renewable Sdn Bhd of 10.02-megawatt peak at Gebeng, Kuantan. After almost 4 years of production, the performance of VRSB Solar Plant, Gebeng is decreasing due to the decreasing of the production. Therefore, there is need to evaluate the performance and understand the operation and maintenance requirement. Because of that, The Performance Analysis of Solar Plant in Gebeng Project is carry out to develop the simulation model of Gebeng Solar Power plant by using RET Screen Software and evaluate the real data of plant, to simulate the system and compare the results with actual data obtained from the plant with different criteria of solar panel and to evaluate the performance of the power plant and propose a better operation system and maintenance activities in the solar plant. This project will involve the discuss about solar energy: technology of solar, type of brand of panel solar, annual electricity production, solar radiation, temperature and humidity, degradation of solar, equipment failure and simulation by using the software. For this project, the simulation by using RET Screen Software that will estimate the performance level of solar plant and compare the electricity production with different criteria of solar panel such as the type and brand solar panel and the degree of the slope of solar panel. The obtained results reveal that the implemented solar panel in VRSB Solar Power Plant are the best type, brand and degree of slope of solar panel, but the maintenance activities must be properly planning to sustain the plant.